ETNOBOTANI ‘ HOINU’ ABELMOSCHUS ESCULENTUS (l.) MOENCH. : PEMANFAATAN, PROSPEK DAN PENGEMBANGANNYA, DI SULAWESI TENGGARA - Rahayu, Mulyati (Jurnal Teknologi Lingkungan, 2008)
Abelmoschus esculentus (L,) Moench. (Malvaceae) is non-indeginous speciesin Indonesia but people in Wawonii Island, Southeast Sulawesi, was long enough traditionally domesticated and used it. The utilization of this plant teds increase but effort on intensively cultivated was still limited. Because of its potency a study of Abelmoschus esculentus especially in relation with daily necessity of people in Wawonii is needed. The status, description and other information related with its utilition were discussed.